A homotopy between the solutions of the elastic and the elastoplastic boundary value problem - Lang, Holger; Dressler, Klaus; Pinnau, René; Bitsch, Gerd (2006)
In this article, we give an explicit homotopy between the solutions (i.e. stress, strain, displacement) of the quasistatic linear elastic and the quasistatic nonlinear elastoplastic boundary value problems, where we assume a linear kinematic hardening material law. We give error estimates with respect to the homotopy paramete
UnivIS-Import:2016-06-30:Pub.2006.tech.FT.ltd.ahomot
Keywords: Elastic BVP; elastoplastic BVP; variational inequalities; rate-independency; hysteresis; linear kinematic hardening; stop- and play-operator; homotopy